Reclaiming Haiti's Futures : Returned Intellectuals, Placemaking, and Radical Imagination - Dubuisson, Darlène Elizabeth (Rutgers University Press, 2024)
Haiti was once a beacon of Black liberatory futures, but now it is often depicted as a place with no future where emigration is the only way out for most of its population. But Reclaiming Haiti's Futures tells a different story. It is a story about two generations of Haitian scholars who returned home after particular crises to partake in social change. The first generation, called jenerasyon 86, were intellectuals who fled Haiti during the Duvalier dictatorship (1957-1986). They returned after the regime fell to participate in the democratic transition through their political leadership and activism. The younger generation, dubbed the jenn doktè, returned after the 2010 earthquake to partake in national reconstruction through public higher education reform. An ethnography of the future, the book explores how these returned scholars resisted coloniality's fractures and displacements by working toward and creating inhabitability or future-oriented places of belonging through improvisation, rasanblaj (assembly), and radical imagination. By centering on Haiti and the Caribbean, the book offers insights not just into the Haitian experience but also into how fractures have come to typify more aspects of life globally and what we might do about it.
Frontmatter -- Contents -- Preface -- Note on the Text -- Abbreviations -- Chronology -- Introduction -- PART I Fractures -- 1 Colonial Ruptures in the Caribbean and the Displacement of Haitian Intellectuals -- 2 Internal Displacements: Tracing the Generational Aspects of Exile and Diasporic Homecomings -- 3 The "Crisis Factory": Improvising Place in the (State) University of Haiti -- PART II Sutures -- 4 Rasanblaj: Assembly beyond Coloniality's Fractures -- 5 Imagining Emancipatory Caribbean Futures -- Coda -- Acknowledgments -- Notes -- References -- Index -- About the Author
Machine-generated record
JSTOR
Keywords: SOCIAL SCIENCE / General; Social change -- Haiti -- History -- 20th century; Social change -- Haiti -- History -- 21st century; Return migrants -- Haiti; Haitian diaspora -- History -- 20th century; Haitian diaspora -- History -- 21st century; Haiti -- 20th century; Haiti -- 21st century